PERFORMANCE OF LAYER HEN FED FERMENTED Jatropha Curcas L. MEAL SUPPLEMENTED WITH CELLULASE AND PHYTASE ENZYME - Sumiati, S.; Mutia, R.; Darmansyah, A. (Diponegoro University, 2012)
The objective of the experiment was to study the effect of feeding fermented Jatropha curcas L.meal (JCM) supplemented with cellulase and phytase on the performances of ISA-Brown laying henaged 25-30 weeks. The Jatropha curcas meal was fermented using Rizhopus oligosporus. In this study200 laying hens were used and distributed to 5 treatments and 4 replications in Completely RandomizedDesign. The diet treatments were: R0 = control diet (without JCM), R1; diet contained fermented JCM7.5%, R2; diet contained fermented JCM 7.5% + celullase 200 g/ton, R3; diet contained fermented JCM7.5% + phytase 200 g/ton and R4; diet contained fermented JCM 7.5% + cellulase 200 g/ton + phytase200 g/ton. The parameters observed were feed consumption, hen day egg production, egg massproduction, egg weight and feed conversion ratio. The results showed that feeding fermented JCM 7.5%,both enzyme supplemented as well as unsupplemented significantly decreased (P<0.05) the feedconsumption, hen day egg and egg mass production. However, the treatments did not influence the eggweight. Supplementation of cellulase (R2) or phytase (R3) improved the feed conversion ratio with thevalue as same as the R0 diet.